Epidemiology, aetiology and outcomes of acute pancreatitis: A retrospective cohort study. (November 2015) - Nesvaderani, Maryam; Eslick, Guy D.; Vagg, Daniel; Faraj, Shadi; Cox, Michael R.
Abstract: Background: Acute pancreatitis is a common acute surgical presentation in Western Society. The causes and pattern of pancreatitis has not been previously documented for Western Sydney. As Western Sydney contains many areas of low socio-economic status with an expected high level of alcohol abuse, it was hypothesised that alcoholic pancreatitis would be more prevalent in this population. The aims of this study were to determine the epidemiology, aetiology and outcomes of acute pancreatitis. Methods: A retrospective analysis of patients presenting with acute pancreatitis to four tertiary hospitals over a four-year period was undertaken. Results: 932 patients presented with acute pancreatitis with a median age of 50 years (range 16–95); 470 (50.4%) were female. Almost half had gallstones (40%), 25.6% idiopathic, 22% alcohol induced and 3.9% post ERCP. 69 (7.4%) of patients were admitted to ICU/HDU, with a median length of stay in ICU was 6 days (range 1–106). 85 (11.1%) patients had severe pancreatitis (score ≥ 3). Mortality in this study was 1% (9). Conclusion: The majority of patients with acute pancreatitis in Western Sydney present with mild disease and have a low risk of morbidity or mortality. The ratio of gallstone to alcohol aetiology was 2:1. Idiopathic pancreatitis is responsible for more cases than expected. Highlights: It is important to understand the epidemiology, aetiology and outcomes for acute pancreatitis. A sample of 932 patients with acute pancreatitis were analysed in this study. Most patients present with mild disease and have a low risk of morbidity/mortality.